Non-Hodgkin Lymphoma Mimicking Lymphadenitis Tuberculosis: Don’t Miss It in Tuberculosis Endemic Area - Haryati, Haryati; Prenggono, Muhammad Darwin; Oktaviyanti, Ika Kustiyah; Kusumawardani, Devi A (Asian Pacific Journal of Cancer Care, 2026)
Introduction: In TB-endemic areas, lymphadenopathy may be misdiagnosed as TB and disguise lymphoma. Specialized professionals or multidisciplinary teams (MDT) must collaborate to solve the diagnostic challenge. Case Presentation: We present a case of a 27-year-old woman who was initially diagnosed with TB cervical lymphadenitis by open biopsy. After 4 months of anti-tuberculous drugs, the neck wound after surgery worsened, and frequently, air bubbles and food emerged. TB medication was discontinued, and the following chest and head-neck CT scan revealed a soft tissue mass 5.7 x 9.5 cm infiltrating cutis in the pre-sternal region with the destruction of the sternum and multiple lymph nodes in the thorax, axilla, and cervical area, as well as anaplastic large cell lymphoma, a rare type of non-Hodgkin lymphoma with positive Ki67, CD45, and CD3, and negative CD20 and CK from re-biopsy. An MDT meeting concluded non-Hodgkin’s lymphoma, Ann Arbor stage IVB. Cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) treatment was given. After six cycles of chemotherapy, symptoms improved, and the wound healed. Conclusion: It highlights, misdiagnosis of lymphoma as tuberculosis delays treatment and affects prognosis. Thus, repeated investigations after anti-TB treatment failed, and the MDT meeting helped clinicians diagnose and treat patients.